Analysis of Euphemism and Dysphemysm Debate of Presidential Candidates of The Republic of Indonesia in 2024-2029 Najwa Shihab Youtube Channel - Sinaga, Dermawati; Ahada Wahyusari; Dody Irawan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research is intended to identify various forms of euphemism and dysphemism in the debate of presidential candidates of the Republic of Indonesia in 2024-2029. The method used in this study is a qualitative descriptive approach. The source of data in this research is the video of the debate of the presidential candidates of the Republic of Indonesia in 2024-2029 published on Najwa Shihab's YouTube channel. The data collection method used in this study is a documentation technique. The instrument used in this study is the researcher himself. The euphemisms and dysphemes found are the use of abbreviations, the use of absorbed foreign words, terms, metaphors, and perifrasa. The function of euphemism used in the use of euphemisms is politeness and comfort. Meanwhile, the function of dysfemism used is to express swearing or swearing.